2017
DOI: 10.1089/acm.2017.0095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroalcoholic Extract of Capsella bursa pastoris on Early Postpartum Hemorrhage: A Clinical Trial Study

Abstract: Compared with the mere administration of oxytocin, sublingual Capsella bursa drops appear to be effective in reducing PPH in this study. Further research regarding the efficacy and safety of various doses of Capsella bursa pastoris is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 8 publications
0
19
0
3
Order By: Relevance
“…Other studies showed that the extract of CBP is an effective drug on control of non-structural heavy menstrual bleeding and postpartum haemorrhage [21,22] (1,2). Our results also showed a decrease in duration of bleeding but there was not the difference between CBP and control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that the extract of CBP is an effective drug on control of non-structural heavy menstrual bleeding and postpartum haemorrhage [21,22] (1,2). Our results also showed a decrease in duration of bleeding but there was not the difference between CBP and control group.…”
Section: Discussionmentioning
confidence: 99%
“…(Brassicaceae) commonly known as 'shepherd's purse' is an edible plant with young leaves and roots that are eaten raw or cooked in Asian and European countries [17,18]. This plant is one of the herbs traditionally used to control different types of bleeding, particularly uterine bleeding, in many cultures [13,[19][20][21][22][23]. CBP was referred to as "blood plant" in the middle ages and used to control bleeding anywhere in the body either orally (extract and decoction) or topically [24].…”
Section: Introductionmentioning
confidence: 99%
“…bursa-pastoris hydro-alcoholic extract (sublingual drops) along with the oxytocin infusion was given to the intervention group. Tannins and flavonoids of C. bursa-pastoris, which compose the large portion of active ingredients, seems to mediate the anti-hemorrhagic effect through the contraction of uterus smooth muscles and the strong antioxidant activity, respectively (16). The therapeutic dose of the extract are 5-8 g/day, and no toxic effects have been reported in the mentioned range.…”
Section: Brownea Grandiceps Jacq (Fabaceae)mentioning
confidence: 96%
“…The therapeutic dose of the extract are 5-8 g/day, and no toxic effects have been reported in the mentioned range. Higher doses (>25 g/day) should be avoided because of the probable side effects (16).…”
Section: Brownea Grandiceps Jacq (Fabaceae)mentioning
confidence: 99%
“…[5,[21][22][23][24][25][26] In a follow-up study, the prevalence rate of moderate-to-severe knee OA increased from 3.7% in the initial survey to 26.7% over the next 11 years. [6,[27][28][29][30][31][32][33][34] Prevalence rate of OA is reported to be 16.6% in the urban area of Iran. [7,[35][36][37][38] The most important characteristic of OA is a gradual degeneration of the joint cartilage, which is associated with bone hypertrophy (osteoporosis and subcutaneous bone sclerosis) and thickening of the joint capsule.…”
Section: Introductionmentioning
confidence: 99%